Warm compresses Against Pain Giving Birth In Practice Independent Midwives HJ. Zurahmi 2019: Warm compresses Against Pain Giving Birth In Practice Independent Midwives HJ. Zurahmi 2019 - Eka Maya Saputri (Journal of Midwifery and Nursing, 2020)
The most tiring and severe time, and most pregnant women feel pain or pain during labor is the first phase of the latent phase and active phase. One method in reducing labor pain is a warm compress. The use of compresses is Easier and more practical through procedures without having to undergo training. Warm compresses are roomates can vasodilating increase of the local temperature of the skin thereby increasing circulation to the tissues to reduce muscle spasms and reduce pain. This case study was Carried out with the aim of giving Midwifery care to women by giving warm compresses and to Determine the effect of warm compresses on pain. Case study method for women with childbirth pain, to Overcome this problem, a warm compress is done. The final report is done at BPM Hj. Zurahmi York City, Midwifery care for women with back pain was done 8 times of care for 1 day on July 5, 2019. After Midwifery care of 8 times for Patients, the results Obtained in the last study were back pain experienced by mothers can be reduced and resolved. It is hoped that it can Become an entry for BPM in the management of labor pain in the first stage of the latent and active phases the which can be applied at the BPM by using a warm compress